PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS LEARNING CYCLE 5-E DILENGKAPI PETA KONSEP PADA MATERI SISTEM PENCERNAAN MANUSIA UNTUK SMP - Nilawati,, Nilawati,; Indriati, Gustina; Nerita, S.Pd, M.Pd, Siska (Pendidikan Biologi, 2014)
ABSTRACT Worksheet in the school is not suitable yet with learning cycle target. Worksheet which used in the school can help teacher  in learning process but not allof student use it, they is not intresting with it. Some of students are not understand the material.  In learning process is needed suitable media and teaching material. One of  teaching materials that can  use is worksheet. This research  aim  to produce worksheet based learning cycle 5-E completed mind map at human digestyfus system at junior high school and produce valid and   pratical   worksheet. This research is development research  which  uses  4-D  models  and  consist  of  4  stages  are  define,  design,  develop  and disseminate but in this research disseminat is not used. Kinds of the research is  primer data that consist validation result and practicality. The tes result of validity of students worksheet based learning cycle 5-E complete mind map by validator show that this  worksheet is very valid with main score is 89,20% . the test of result practicality of students worksheet based learning cycle 5 -E complete with mind maping by teacher show that this worksheet at practical criteria with main score 89,20% and then the test result of practicality that done by students show that the students worksheet at   practical criteria   with main score   91,25%. So that, can be concluded students worksheet based learning cycle 5-E at human digestyfus system is very valid and very practical.